Big bath accounting and CEO turnover: the interplay between optimal contracts and career concerns - Tim Hensel; Jens Robert Schöndube (Journal of Business Economics, 2022)
Following executive turnovers big bath accounting is often observed. We investigate a new manager's earnings management incentives in his first year in office in a two-period model with career concerns and earnings' lack of timeliness. We determine the optimal incentive contract and decompose the manager's equilibrium earnings management into two components: an explicit incentive resulting from the compensation contract and an implicit incentive from career concerns. While career concerns always motivate the manager to shift earnings backwards, the optimal contract induces the manager to either shift earnings forwards or backwards. In particular, we show that with optimal contracts a "negative" big bath may result in equilibrium, i.e., the manager may inflate earnings after a CEO turnover. We demonstrate how the optimal contract and the equilibrium earnings management strategy depend on the earnings' timeliness, the precision of the initial information about the manager's ability and the intensity of competition for CEOs. Our results may help to explain why big bath accounting after a CEO turnover is observed in many but not in all cases.
Keywords: D82; G34; M12; M41; 650; Earnings management; Big bath accounting; Career concerns; Contracting; CEO turnover